Analisis Kinerja Pegawai Dinas Perumahan dan Kawasan Pemukiman Berdasarkan Pengaruh Motivasi Kerja dan Disiplin Kerja - Meswantri, Meswantri; Lukito, Daniel (CV. ITTC INDONESIA, 2024)
Employee performance is one of the indicators that can be used to assess employee performance in an agency. Employee performance measurement can be measured by several parameters such as work motivation and work discipline. Based on this, the purpose of this study is to determine the effect of work motivation and work discipline simultaneously and partially on employee performance in the Housing and Settlement Service. The analysis method in this study uses multiple linear regression methods based on variables (X1) Work Motivation and (X2) Work Discipline on (Y) Employee Performance. The results of the study indicate that work motivation is significant and has a positive relationship to employee performance with a T count of 2.401> T table 2.064. The results of the analysis are also seen based on the variable (X2) Work discipline has a significant effect and has a positive relationship direction to employee performance with an F count of 2.227> F table 2.014. The results of the positive determination carried out by work motivation and work discipline of 1.90 while the remaining 4.18 is influenced by other variables not examined in this study. Based on this, the analysis carried out can contribute to improving management in an organization